Meningkatkan Hasil Belajar Keperawatan Dasar Melalui Metode Pembelajaran Problem Base Learning (PBL) Mahasiswa Tingkat I Akper Bhakti Husada Cikarang Tahun 2018/2019 - Lina Marlina; Rini Nurdini (JURNAL KESEHATAN BHAKTI HUSADA, 2020)
Background: Learning outcomes for basic nursing courses for two years at Akper Bhakti HusadaCikarang still do not meet the minimum graduation limit for TA. 2016/2017 as many as 13% of thetotal 59 students and for TA. 2017/2018 as many as 23% of 70 students, while the minimum targetfor graduation is 80%. So we need an effective learning method that can improve student learningoutcomes in basic nursing courses. Problem Based Learning (PBL) we can say as a learning modelthat prepares students to think critically and analytically, and seeks and uses appropriate learningresources to deal with an existing problem. The tutorial (tutoring) is academic assistance or tutoringby tutor to students (tutee) to help smooth the independent learning process of individual students orgroups related to teaching materialMethod: This research is a classroom action research in the form of a descriptive level for first-levelstudents for basic nursing courses.Results: The average value of the process scores for students scenario 1, 2 and 3 have exceeded thevalue of the graduation limit or expected value. Pre-test scores for each scenario have not reachedthe expected value, still below 68. The average post-test scores of students have been more than theexpected value.Conclusion: Tutorial methods can improve their ability to create alternatives and solve problems. Itis recommended that the tutorial method can be applied to other subjects besides basic nursing. Theselection of respondents / students studied must be chosen that has a level of intelligence or abilitythat is not much different.